Analysis on Elements Impacts Ecological Behaviour on Psychology Education: Understanding the Interplay between Individuals and their Environment (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Ecological psychology is the study of communication between individuals and their physical aspects. In this process, individuals change their behaviour, and their environments and knowledge are changed by their environment. It conducts theory, studies, and practice aimed to create environment more humane and getting better human relationships with the usual environment. In view of the giant speculation society makes in the physical ecology and the cost of misuse nature and natural resources, ecological psychology is a key component of both human and ecological welfare.